Regulatory interplay between LEAFY, APETALA1/CAULIFLOWER and TERMINAL FLOWER1: New insights into an old relationship. (3rd October 2017) - Serrano-Mislata, Antonio; Goslin, Kevin; Zheng, Beibei; Rae, Liina; Wellmer, Frank; Graciet, Emmanuelle; Madueño, Francisco
ABSTRACT: The gene regulatory network comprised of LEAFY (LFY), APETALA1 (AP1), the AP1 paralog CAULIFLOWER (CAL), and TERMINAL FLOWER1 (TFL1) is a major determinant of the flowering process in Arabidopsis thaliana . TFL1 activity in the shoot apical meristem provides inflorescence identity while the transcription factors LFY and AP1/CAL confer floral identity to emerging floral primordia. It has been thought that LFY and AP1/CAL control the onset of flowering in part by repressing TFL1 expression in flowers. However, in the June issue of Plant Physiology, we reported that LFY and AP1 act antagonistically in the regulation of several key flowering regulators, including TFL1 . Specifically, TFL1 transcription was suppressed by AP1 but promoted by LFY. Here, we present additional evidence for the role of LFY as an activator of TFL1 and propose that this regulatory activity is pivotal for the indeterminate growth of the SAM during the reproductive phase of development.